Epidemiological and Serological Aspects in Canine Toxoplasmosis in Animals with Nervous Symptoms - Brito, Adriana Falco de; Souza, Luiz Carlos de [UNESP]; Silva, Aristeu Vieira da [UNESP]; Langoni, Hélio [UNESP] (Instituto Oswaldo Cruz, Ministério da Saúde, 2002)
The presence of anti-Toxoplasma gondii IgM and IgG antibodies was studied in samples of blood serum taken from eighty dogs with nervous symptoms at the Serviço de Enfermidades Infecciosas dos Animais, Faculdade de Medicina Veterinária e Zootecnia, Unesp, Botucatu, São Paulo, Brazil. The frequency of IgG titers were 16 (13.7%), 64 (13.7%), and 256 (5%), and for IgM titers were 16 (7.5%), 64 (15%), and 256 (8.7%). Positive reactions were more frequent in the older animals, males, from a rural environment, in constant contact with small animals, principally birds and rodents. There was a higher frequency of a positive reaction in dogs fed with kitchen food, especially in those fed with raw ingredients. The most common neurological pictures were alterations in consciousness, in movement, and in the hand-cart test. The percentage of reagents with specific IgM antibodies was high, indicating active infections, but the possibility of co-infection with the distemper virus can not be discarded, and this may be a predisposing factor for toxoplasmosis infection, once the distemper virus has a potent immunosupressive action.
Keywords: toxoplasmosis; canine; serology; epidemiology; nervous symptomology